Disability, higher education and e-learning: Moving beyond accessible web design - Kent, Michael; Ellis, K.; Pitman, T.; McRae, L.; Latter, N. (Routledge, 2019)
The concerns raised here are further in Manifestos for the Future of Critical Disability Studies.